Sarcosporidiasis on Rats in Smallholder Oil Palm Plantations in Deli Serdang Regency, North Sumatra - Makhrani Sari Ginting; Henry Budi Hasibuan; Sulaiman Ginting (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rats are significant pests in oil palm plantations, attacking nearly all growth stages of the plants and causing damage that adversely affects productivity, leading to substantial losses. The protozoan Sarcocystis sp. is a parasite that infects rats and, in sufficient quantities, can cause death in these hosts. This protozoan is naturally present in rats but typically in small amounts. This study aimed to determine the prevalence of sarcosporidiasis (the presence of Sarcocystis sp.) in several rat species inhabiting smallholder oil palm plantations in Deli Serdang Regency, North Sumatra. Rat sampling was conducted from June to August 2025 using baited traps. The captured rats were then identified and categorized by species, sex, and weight. Sarcocystis sp. infection was detected by observing the presence of 'milky white threads' in the muscles, particularly in the rats' legs. The data obtained were analyzed both descriptively and quantitatively. Results showed that two rat species were captured: Rattus argentiventer and Rattus tiomanicus. Only 29.4% of the captured rats tested positive for the protozoan, of which 63.3% were male and 36.7% were female. All rats testing positive for the protozoan belonged exclusively to the R. tiomanicus species